Changing international relations after the covid-19 pandemic - Grizold, Anton (Teorija in praksa, 2020)
Covid-19 pandemic came during the globalization backlash and accelerated two important millennial mega trends: the changing nature of production and innovation, and the changing global world order and trading system. Although stronger multilateralism was seen as a key approach to tackling the tough global challenges before the global crisis, the national responses at the start of Covid-19 have crowded out multilateral and even regional initiatives and revitalised the role of the state. A growing gap between national, regional and multilateral responses to Covid-19 challenges the development of global governance and regional integration, as well as the future of the EU and its capacities for international economic and political cooperation. All the dimensions of the complex multifaceted systemic crisis exacerbated by the Covid-19 pandemic are, however, still to be established, and their impacts on individual countries as well as on international relations continue to be an important topic of discussion and research
Keywords: Covid-19; Crises; Epidemics; Epidemije; globalizacija; International relations; Krize; Mednarodni odnosi; multilateralizem; nacionalna država; odzivi; pandemije; politične spremembe